Conflict resolution strategies in classical antiquity and Yoruba society (2019)
As long as man lives and as long as societies relate together, conflict is inevitable. Therefore, for peace to reign in various communities, traditional societies had developed a well-defined structure for resolution of conflicts. In ancient times, particularly in Rome and Yoruba land, conflict resolution was done in conjunction with the council of chiefs and elders. Existing studies on the resolution of conflicts have mainly focused on the modern methods which, over the years, have not yielded any significant result because their modes of Operation are at variant with the custom and culture of the people. This paper examines how the traditional Romans and Yoruba resolved conflicts through the use of traditional rulers, that is, the paterfamilias and Mo ga ji' (family head), Baale (compound head), Baa' le ‘(community head) and the O ba (town head). It explores how such traditional role could be brought to bear in the Contemporary society, where ethno-religious and resource control conflicts which have resulted in wanton destruction of lives and properties in many countries of the world. This study adopts a comparative approach to highlight how conflicts were settled at various levels of administration in ancient Rome and the traditional Yoruba society. The paper concludes by suggesting how the ancient methods can be re- incorporated into the modern methods of conflict resolution in various communities, especially Nigeria.